Sedimentation rate and nutrients at coral reef of Talang-talang Island, Sematan, Sarawak - Lee, Xue Li (Universiti Malaysia Sarawak, UNIMAS, 2012)
A study was conducted to determine the rate of sedimentation and nutrients at coral reef area in Talang-Talang Island from July 2011 to April 2012. The sedimentation rates were determined by setting up sedimentation traps at three selected stations and water samples were collected at four selected stations within the coral reef area. The sediments collected were analysed to determine particle size while water samples were collected to analyse total suspended solids (TSS) and nutrients. The mean sedimentation rates ranged from 5.35 - 13.95 mg/cm²/day in November 2011 and from 77.78 - 136.27 mg/cm²/day in April 2012. The mean concentration of TSS ranged from 21.62±4.74 to 27.07±3.33 mg/l. Analysis on the composition of sediment shows that the percentage of sand ranged from 24.61 to 52.79 %, silt ranged from 44.88 to 68.20 % and clay ranged from 2.33 to 24.67 %. Mean concentration of orthophosphate, nitrate-N and ammonia-N ranged from 0.02 – 0.09 mg/l, 0.01 - 2.90 mg/l and 0.45 – 1.23 mg/l respectively. Sedimentation rates at Talang-Talang Island exceeded the natural sedimentation rates especially at Station 2. High sedimentation rates and nutrients concentration were influenced by environmental factors and human activities but they affected the growth, reproduction and metabolism of corals.